Reconstructing the thermal history of fish juveniles using stable oxygen isotope analysis of otoliths - Morat, Fabien; Blamart, Dominique; Bounket, Bernadette; Argillier, Christine; Carrel, Georges; Maire, Anthony (Frontiers in Environmental Science, 2023)
Characterizing the thermal habitat of fish is key to understanding their ecological requirements in order to make appropriate management plans for the preservation of fish populations in the context of climate change. Little is known about the thermal habitat of the early life stages of fish (larvae and juveniles), as most methods have been designed for large, easily handled individuals. In particular, the study of otoliths holds great promise for unveiling the early thermal history of fish, although it is challenging to implement due to the very small size of the biological material. The stable oxygen isotope content (δ 18 O) of biogenic carbonates (such as otoliths) can be used to reconstruct the life temperature of fish individuals. However, relationships between δ 18 O of otoliths and ambient temperature are scarce and mainly developed for commercial species. In this study, we assessed the δ 18 O of juvenile European chub (Squalius cephalus, Linnaeus 1758) living in a section of the lower Rhône River in France. The δ 18 O of otoliths showed significant relationship with ambient temperature (δ 18 Ooto(VPDB) -δ 18 Ow(VPDB) = 33.391 -0.2641 * T(°C)), and the relationship between temperature and the fractionation factor (α) was 1000 ln α = -43.472 + 21.205 (1000/T(K)). As expected, back-calculated temperatures from these equations were in much better agreement with the measured in situ temperatures than previously published equations.This equation is the first to be developed for leuciscid fish in Europe and the second in the world.